Lysophosphatidic acid-3 receptor-mediated feed-forward production of lysophosphatidic acid: an initiator of nerve injury-induced neuropathic pain - Aoki Junken; Chun Jerold; Inoue Makoto; Nagai Jun; Uchida Hitoshi; Ma Lin; Ueda Hiroshi (SAGE Publishing, 2009)
Abstract Background We previously reported that intrathecal injection of lysophosphatidylcholine (LPC) induced neuropathic pain through activation of the lysophosphatidic acid (LPA)-1 receptor, possibly via conversion to LPA by autotaxin (ATX). Results We examined in vivo LPA-induced LPA production using a biological titration assay with B103 cells expressing LPA1 receptors. Intrathecal administration of LPC caused time-related production of LPA in the spinal dorsal horn and dorsal roots, but not in the dorsal root ganglion, spinal nerve or sciatic nerve. LPC-induced LPA production was markedly diminished in ATX heterozygotes, and was abolished in mice that were deficient in LPA3, but not LPA1 or LPA2 receptors. Similar time-related and LPA3 receptor-mediated production of LPA was observed following intrathecal administration of LPA. In an in vitro study using spinal cord slices, LPA-induced LPA production was also mediated by ATX and the LPA3 receptor. Intrathecal administration of LPA, in contrast, induced neuropathic pain, which was abolished in mice deficient in LPA1 or LPA3 receptors. Conclusion These findings suggest that feed-forward LPA production is involved in LPA-induced neuropathic pain.